Planlægning af motion- og idrætsanlæg med brug af evidens - Hjort, Mikkel (Forum for Idræt, 2014)
Planlægning af motion- og idrætsanlæg med brug af evidens (Planning of sport and recreational schemes with implementation of evidence) The general health of the Danish population has over the last decades been an important topic in Denmark, and the subject is not getting less important, as the development of lifestyle diseases continues to increase. This increasing public emphasis on general health is reflected also in contemporary architecture, where new projects and construction plans within cultural and sport schemes often have great visions to improve the general health conditions in the population today. Traditional methods are often used in the process of development, and therefore the question is if the visions can be accomplished in new schemes? Evidence is described as the missing tool before architecture can evolve in response to the present conditions. There are many ways to assemble evidence. Some examples include evaluation of projects, data collection or research in other disciplines, such as sociology, health sciences and natural sciences. Scientists have put focus to the lack of connection between the operating architects and the academic environment at the university, and the book Design Informed points out that there is no use of evidence in the process of planning today. Therefore the newest research does not reach the operating architects and new projects are designed using traditional methods. The purpose of this article is to discuss different methods to secure that the newest evidence; research and knowledge from other sciences are transferred and used in the planning of new projects involving sport and recreation.